2012
DOI: 10.1093/geronb/gbs076
|View full text |Cite
|
Sign up to set email alerts
|

Does Social Activity Decrease Risk for Institutionalization and Mortality in Older People?

Abstract: Collective social activity may be associated with a reduced risk for mortality and institutionalization in older people. Further studies on the mechanisms underlying the association between social activity and health are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 47 publications
4
32
0
Order By: Relevance
“…Our results suggest that social activities and health have a reciprocal causal relationship in the group of older adults with normal cognitive function, and a causal relationship was found in social activities as a predictor of health for older adults with mild and moderate/severe cognitive impairment. A major finding of this study that older adults' participation in social activities is a predictor of better health is consistent with previous studies indicating that social activities have positive effects on physical [3,4], cognitive [5,7] and subjective well-being [8] for older adults. Even for those who are cognitively impaired, participation in social activities is a major requirement for maintaining and promoting health.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results suggest that social activities and health have a reciprocal causal relationship in the group of older adults with normal cognitive function, and a causal relationship was found in social activities as a predictor of health for older adults with mild and moderate/severe cognitive impairment. A major finding of this study that older adults' participation in social activities is a predictor of better health is consistent with previous studies indicating that social activities have positive effects on physical [3,4], cognitive [5,7] and subjective well-being [8] for older adults. Even for those who are cognitively impaired, participation in social activities is a major requirement for maintaining and promoting health.…”
Section: Discussionsupporting
confidence: 92%
“…In Rowe and Kahn's successful aging model, active participation in social activities is emphasized as a key component for successful aging in addition to preventing diseases disability and maintaining physical cognitive function [2]. As the population rapidly ages, many cohort studies in Europe and the United States (US) have reported that participating in social activities has positive health outcomes for older adults [3][4][5]. Specifically, a 17-year longitudinal study reported that collective social activities reduced the risk of mortality and institutionalization among older adults [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, various types of leisure activities − e.g. productive [13], solitary [13,14], social [15] and physical [14,16] − have been found to predict older adults' wellbeing, health and survival. Hence, persons with hearing problems may be at higher risk 12 for adverse health outcomes following withdrawal from leisure activities.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the emphasis on social participation in old age are mostly related to evidence that being socially active is associated with well-being, quality of life and lower risk of morbidity and mortality 3,4 . Findings have shown relationships between higher level of social participation and lower risk of morbidity 5 , disability 6,7 , depressive symptoms 8 , and cognitive impairment 9 .…”
Section: ▄ Introductionmentioning
confidence: 99%